Dynamic Administration: The Collected Works of Mary Parker FollettDynamic Administration; The Collected Works of Mary Parker Follett, MetcalfHenry C. and UrwickL., Eds. New York: Harper and Brothers Publishers, 1941, 320 pp. - Ferry, Diane L. (Academy of Management Review, 1986)
The article reviews the book ?Dynamic Administration: The Collected Papers of Mary Parker Follett,? edited by Henry C. Metcalf and L. Urwick.